Evaluation of the antiulcer effect of the aqueous and methanolic extract of the seeds of lupinus mutabilis sweet (tarwo, chocho) in rats - Castañeda, C. B. (2022)
In the present research, we have evaluated the effect of Lupinus mutabilis Sweet's seed, as watery and methanolic extracts on the gastric mucous of rats, following the Lee's method. Indometacin in doses higher than 50 mg per kg of weight causes lineal lesions, enlarging and dilatation of small intestine; partial obstruction, acute and chronic transmural granulomatous inflamation; abscess in the intestine's crypts and fibrosis. 2000 mg/kg of weight of the watery extract of the Lupinus was administered by mouth and 400 mk/kg of the methanolic extract by the same way.We use four groups of ten male rats each one with 250 g of weight approximately that were previously conditionated in our laboratory supplying food and water ad libitum. The animals were distributed in four groups in aleatory way and they received saline solution, ranitidine, watery extract of Lupinus and methanolic extract of Lupinus respectively. All substances were administered by oral route 30 minutes before to administer Indometacina to the animals that were in fast for 48 hours. Five hours later the animals were sacrificed and submitted to laparotomy in order to observe the macroscopically anti ulcerogenic effect that was evident and statistically significant with a value of p= 0,0013; microscopically was p= 0,0053.The anti ulcerogenic effect was: 57 % for Ranitidine, 60 % for watery extract of Lupinus and 40 % for methanolic extract of Lupinus; besides we could observe normalization of gastric mucous architecture and lowing of granulocites inftltration.We found that both extracts of Lupinus protected the gastric mucous from the lesions caused by Indometacina and could be an alternative for the treatment of gastroduodenal ulcer.